Rehabilitasi Korban Penyalahgunaan Narkoba Melalui Metode Narcotic Religious (Studi Kasus: Yayasan Grapiks Cileunyi) - Yumna Rais; Ai Hidayatunnajah; Muhammad Eko Nugroho (Journal of Society and Development, 2021)
One of the problems in Indonesian society is drug abuse. Drugs stands for Narcotics, Psychotropics and other addictive substances. In addition, drugs are also often referred to as NAPZA which stands for Narcotics, Psychotropics and other addictive substances. And one of the remedies that can be done in overcoming drugs is to carry out rehabilitation. Rehabilitation is a way of restoring to return to its original position, repairing deformed limbs, disaster victims so that they become useful people and gain a place in society. In rehabilitation, there are many approaches or therapies that can be applied to victims of drug abuse. One of the methods used at the Grapiks Cileunyi Foundation is to use Narcotic Religious in which there are 7 steps, namely Intention, Repentance, Prayer, Ikhtiar, Tawakkal, Gratitude, Istiqomah. This method is the first breakthrough in the world of therapy carried out at the Foundation. With this method it is also expected that victims of drug abuse can raise awareness in understanding religion, increase religious knowledge, live calm and have a purpose, and when they have problems they can involve Allah at every step of the way.